Minority Stress and Experience of Sexual Violence Among Men Who Have Sex With Men in Hanoi, Vietnam: Results From a Cross-Sectional Study - Hershow, Rebecca B. (Journal of interpersonal violence, 2021)
Men who have sex with men (MSM) are highly vulnerable to sexual violence, a known driver of HIV infection. Homosexuality stigma may be a unique risk factor for sexual violence among MSM. In this study, we examine the relationship between homosexuality stigma measures and sexual violence in the last 12 months using a minority stress framework. MSM were recruited using convenience and snowball sampling. Participants completed an interviewer-administered survey and provided blood samples for HIV testing. Bivariable associations were tested between self-reported experience of sexual violence in the last 12 months and homosexuality stigma measures using odds ratios (ORs) produced by Cochran–Mantel–Haenszel Statistics. A logistic regression model for each type of minority stress was built to conduct the multivariable analyses with independent covariates. Of 202 MSM, 29 (14.4%) participants reported experiencing sexual violence in the last 12 months. About one fourth of participants reported experiencing high enacted (55/202; 27.2%), perceived (52/202; 25.7%), and internalized (60/202; 29.7%) homosexuality stigma. In bivariable and multivariable analyses, enacted homosexuality stigma was the only variable consistently associated with experience of sexual violence in the last 12 months (aOR: 3.5; 95% confidence interval [CI]: [1.5, 8.4]). Sexual violence and homosexuality stigma are highly prevalent among MSM in Hanoi, Vietnam. MSM-targeted HIV prevention interventions in Vietnam should incorporate violence prevention and homosexuality stigma reduction activities. Longitudinal studies are needed to understand how homosexuality stigma influences sexual violence and other HIV risk behaviors among MSM.